WEBGIS-BASED MAPPING OF LAND AND AGRICULTURAL COMMODITIES IN EAST BORNEO - Reza Andrea; Andi Lisnawati; Fajar Ramadhani (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The potential for agricultural land in Indonesia is still vast, making the agricultural sector a primary source of income for the majority of Indonesians. The agricultural sector is widespread across various regions in Indonesia, one of which is East Borneo. As an agricultural area, the majority of the population in East Borneo chooses farming as their livelihood. However, comprehensive agricultural land mapping has not yet been conducted, which could provide essential information about the location of agricultural land, particularly in East Borneo. In this research, a web-based Agricultural Land Geographic Information System has been developed for East Borneo. The geographical information system built can display both spatial and non-spatial data, describing objects based on the Earth’s condition. The object-oriented method was employed in creating this system. It is expected that the development of this Geographic Information System will provide valuable information to the public regarding the distribution of agricultural land locations and their respective areas, especially in the East Borneo. This system will be instrumental in promoting more efficient and sustainable agricultural management in the region.